Switchable generation of multi-wavelength continuous wave and square-wave pluses in a bidirectional Erbium-doped fiber laser. (November 2021) - Cui, Wenxiang; Zhou, Xuefang; Bi, Meihua; Yang, Guowei; Hu, Miao; Wang, Tianshu
Highlights: A bidirectional EFL can generate multi-wavelength continuous wave and square-wave pluses at different cavity loss. Stable square-wave pulse operates in a stable mode-locking state at low threshold. Single wavelength can be achieved, the tunable region is from 1551.59 nm to 1570.08 nm with a span of 19 nm. Abstract: We present a switchable generation of multi-wavelength continuous wave (CW) and square-wave pluses (SWPs) in a bidirectional erbium-doped fiber laser. The variable attenuator (VA) is used to realize switchable generation of CW and mode-locking pulse. In the multi-wavelength loop (MWL), the laser using the Sagnac loop output single-wavelength, dual-wavelength and triple-wavelength CW by finely adjusting the polarization controllers (PC). In the mode-locked loop (MML), the stable SWPs and harmonic mode-lock (HML) SWPs can be obtained by nonlinear polarization rotation (NPR) technique.